2014
DOI: 10.1186/1471-2458-14-1078
|View full text |Cite
|
Sign up to set email alerts
|

Climatic-driven seasonality of emerging dengue fever in Hanoi, Vietnam

Abstract: BackgroundDengue fever (DF) has been emerging in Hanoi over the last decade. Both DF epidemiology and climate in Hanoi are strongly seasonal. This study aims at characterizing the seasonality of DF in Hanoi and its links to climatic variables as DF incidence increases from year to year.MethodsClinical suspected cases of DF from the 14 central districts of Hanoi were obtained from the Ministry of Health over a 8-year period (2002–2009). Wavelet decompositions were used to characterize the main periodic cycles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
43
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 33 publications
9
43
2
3
Order By: Relevance
“…Here we establish a causal relationship between co‐infection and increased disease severity, as H1N1–DENV co‐infected mice succumbed to infection at otherwise sublethal virus doses. Consequently, co‐infection is a risk factor for severe disease in tropical regions, such as Brazil , Thailand, and Vietnam , where influenza and dengue viruses regularly co‐circulate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we establish a causal relationship between co‐infection and increased disease severity, as H1N1–DENV co‐infected mice succumbed to infection at otherwise sublethal virus doses. Consequently, co‐infection is a risk factor for severe disease in tropical regions, such as Brazil , Thailand, and Vietnam , where influenza and dengue viruses regularly co‐circulate.…”
Section: Discussionmentioning
confidence: 99%
“…Little information, however, exists regarding whether co‐infection of influenza with other acute viruses affect disease outcome. Seasonal influenza A virus and DENV epidemics regularly overlap in several regions, including Brazil , Thailand, and Vietnam . During the 2009 influenza H1N1 pandemic, additional countries, including Nicaragua , Puerto Rico , and India reported cases of co‐infection with DENV, resulting in severe disease .…”
Section: Introductionmentioning
confidence: 99%
“…37,38 In addition, seasonality of enteroviruses with peaks during summer has been described in Korea, Taiwan, and the United States. [39][40][41] The Taiwan study found that enterovirus infection was significantly associated with increasing temperature and humidity, which was consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both dengue and malaria show twice-yearly occurrence in Vietnam with only a single annual rainy peak. 51,52 Similarly, malaria recurs twice a year in southern China with only a single annual moisture cycle. 53,54 Such an explanation fails to explain the difference in duration of stress between the two assemblages reported here.…”
Section: Recurrencementioning
confidence: 99%